Bridging Router to ADSL Modem for Stability Network Connection - Arnes Yuli Vandika; Ruri Koesliandana (Bandar Lampung University (UBL), 2013)
We often use the modem but often also see the modem gets hot, because there is also an increase in the process that uses the entire capacity of the modem. Modem is a device used to convert from analog signals to digital signals. Modem that works in full and will also experience the maximum heat conditions. The modem overheats due to an increase in the connection often dropped out suddenly. This is so the problems that often occur in the modem user. Modem is in meticulous type of ADSL technology. ADSL Modem type is very much in use by home users. Experience using this modem, the modem at the beginning of stable then increase the heat, then drop the connection. The approach we use is the method of approach to the bridge network routers, where the router that will perform the function dial and modem just as a conductor only. The router is a device that is used to skip the lines and network maps.